2002
DOI: 10.1002/1099-0682(200210)2002:10<2648::aid-ejic2648>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3,4-Hydroxypyridinecarboxylic Acids as Possible Bidentate Chelating Agents for Aluminium(III): Synthesis and Metal−Ligand Solution Chemistry

Abstract: In view of a possible application to aluminium(III) chelation therapy, 3-hydroxy-4-pyridinecarboxylic acid (3H4P) and 4-hydroxy-3-pyridinecarboxylic acid (4H3P) were synthesised, and their chemical interactions with the metal ion were investigated in aqueous 0.6 m (Na)Cl at 25°C by means of potentiometric titrations. Only mononuclear complexes of the type AlL l H h (l = 1, 2 and 3; h = 0, 1, ..., l) were formed. The qualitative and quantitative results obtained were confirmed by UV spectrophotometry and 1 H NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…This aspect was studied for the Al(III)/4H3P system by keeping constant the pH (3.50) and the ligand‐to‐metal ratio (approximately 2:1) while increasing the total concentration by a factor of nearly 20 (first five lines of Table 1). Under these conditions, according to the equilibrium data from potentiometric measurements in water (T = 25°C, NaCl 0.6 m),52 only the species AlLH 2+ and AlL 2 H 2 + exist in solution; correspondingly, only the peaks produced by these species ( m/z 200, 214, 277 and 303, see Table 3) were observed in the ESI‐MS spectra. For the ESI‐MS results, the ratio R ES‐MS was calculated as follows: (also [M+1] peaks were included).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This aspect was studied for the Al(III)/4H3P system by keeping constant the pH (3.50) and the ligand‐to‐metal ratio (approximately 2:1) while increasing the total concentration by a factor of nearly 20 (first five lines of Table 1). Under these conditions, according to the equilibrium data from potentiometric measurements in water (T = 25°C, NaCl 0.6 m),52 only the species AlLH 2+ and AlL 2 H 2 + exist in solution; correspondingly, only the peaks produced by these species ( m/z 200, 214, 277 and 303, see Table 3) were observed in the ESI‐MS spectra. For the ESI‐MS results, the ratio R ES‐MS was calculated as follows: (also [M+1] peaks were included).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is not surprising, since also in the spectra of solutions containing the ligand alone the relevant peaks were absent or had very low intensities. As a possible explanation, it should be considered that both free ligands are neutral at pH values between 2 and 5, and at pH above 5 they deprotonate to form negatively charged ions;52 this may account for a significant change in the response factor of the free ligand with respect to the metal‐coordinated ligand. As an alternative hypothesis, it might be suggested that the free ligand partially decomposes before reaching the detector by collisions or by oxidation‐reduction phenomena in the ESI source.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies on the design, synthesis and complex formation equilibria of variously substituted hydroxypyridinecarboxylic acids have been presented by the group of Di Marco: these ligands are characterized by two coordinating groups (-OH and -COOH) in various positions (2,3; 3,2; 3,4; 4,3) and differently methylated. [50][51][52][53][54][55] A study of our group on bisphosphonate ligands showed their high efficiency as iron chelating agents, reaching pFe values higher than that of deferiprone. 56 To further improve bisphosphonate chelating properties the conjugation with other strong coordinating groups was proposed.…”
Section: Recent Research Achievements On Iron Chelating Agentsmentioning
confidence: 99%